2020 Winter Simulation Conference (WSC) 2020
DOI: 10.1109/wsc48552.2020.9384094
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Evaluation of Lot Release Policies in a Power Semiconductor Facility – a Case Study

Abstract: Lot release policies, i.e., the decision which lots to start in production, in what quantity and at what time, have a significant influence on fab performance. Recent research focused on closed-loop policies. However, most studies only demonstrated the feasibility in settings with low-mix or low-volume simulation testbeds. In this paper, we focus on a real-world pre-assembly facility in a high-volume and high-mix semiconductor wafer fab. We conduct an in-depth, deterministic discrete-event simulation in two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Thus, slight over-deliveries might occur, which are balanced within the supply chain. We conducted a simulation study to develop approaches for optimal and uniform lot-to-order matching and start date allocation, considering the current product mix, tool equipment, and setup times [11]. The released batches and splits are now evenly distributed.…”
Section: B Phase 2: Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, slight over-deliveries might occur, which are balanced within the supply chain. We conducted a simulation study to develop approaches for optimal and uniform lot-to-order matching and start date allocation, considering the current product mix, tool equipment, and setup times [11]. The released batches and splits are now evenly distributed.…”
Section: B Phase 2: Optimizationmentioning
confidence: 99%
“…However, each adjustment or add-on results in increasing complexity for programming and maintenance. Therefore, we tested a more dynamic, mathematical approach and conducted a discrete event simulation study that showed promising results [11]. Although the current LTOM process is stable and highly automated, IFD seeks to replace the RTD rules with a mathematical solver if the complexity increases.…”
Section: Technical Automation and Optimization Approachmentioning
confidence: 99%
“…AnyLogic yazılımını kullanan bir diğer çalışmada [17] bir hassas imalat firmasının otomatik depolama ve boşaltma sistemlerine yatırım yapması durumunda çıktı performansının ne düzeyde olacağını, etmen tabanlı modelleme ve kesikli olay simülasyonunun birlikte kullanarak modellemişlerdir. Başka bir çalışmada ise, [18] bir yarıiletken plaka üretim fabrikasının ön montaj sürecini, mevcut durumda uygulanan üretim partilerini serbest bırakma politikalarını analiz etmek ve süreci iyileştirmek amacıyla ele almışlardır. Çalışmalarında gerçek süreç verilerine dayalı olarak geliştirdikleri simülasyon modeli ile mevcut durumu analiz etmişler, kaynak kullanım oranı, çıktı miktarı ve zamanında teslimat oranında önemli iyileştirmeler sağlayan öneriler ortaya koymuşlardır.…”
Section: öNceki çAlışmalarunclassified
“…EMICONDUCTOR manufacturing is a complex and costsensitive process characterized by sophisticated devices with short life cycles, fast-changing product mixes, and reentrant product flows comprising hundreds of processing steps on complex and expensive equipment [1]- [3]. The manufacturing process is twofold.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, organizations that follow the Morethan-Moore strategy seek diversification through a broader product mix. However, this approach requires high flexibility and efficient processes, as the simultaneous handling of numerous different products with varying customer due dates is challenging [1], [8]. With the highly complex production planning and control, allocating supply and demand is both a strategic and operational decision [9].…”
Section: Introductionmentioning
confidence: 99%